Petrophyscis study of sandstone core to the accuracy of ultrasonic pulse velocity - Samsuri, Ariffin; Herianto, Herianto; Setyowiyoto, Jarot (2004)
There are few important characteristics of reservoir rocks in petroleum industry that need to be studied for further development. Among them are petrophysic properties such as density, porosity, water saturation and permeability. In this study, tests have been carried out to examine the relationship between petrophysic properties and acoustic velocity of the rock using Ultrasonic Pulse Velocity Method (UPVM). The results of the laboratory test have been used to determine the physical rock properties from acoustic rock velocity data.